1993
DOI: 10.1021/bi00092a003
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of a non-proline cis-peptidyl linkage in a proline-202 .fwdarw. alanine carbonic anhydrase II variant

Abstract: The crystal structure of a human carbonic anhydrase II (CAII) variant, cis-proline-202-->alanine (P202A), has been determined at 1.7-A resolution, indicating that the wild-type geometry, including the cis-peptidyl linkage, is retained upon substitution of proline by alanine. The CO2 hydrase activity and affinity for sulfonamide inhibitors of P202A CAII are virtually identical to those of wild type. However, the substitution of cis-alanine for cis-proline decreases the stability of the folded state by approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 67 publications
5
39
1
Order By: Relevance
“…Importantly, this hypothesis is consistent with the relative unimportance of mutagenesis of Pro313 to Ala313 [13], in that a type II B turn with Gly312 in the i + 1 and Ala313 in the i + 2 position would also be expected to be a competent thrombin-like proteolytic substrate. Alternatively, the type VI turn could be maintained in the P313A variant, as recently observed for a carbonic anhydrase II variant [36]. We suggest that this shift is essential for V, loop cleavage by thrombin, factor Xa, or related proteases.…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, this hypothesis is consistent with the relative unimportance of mutagenesis of Pro313 to Ala313 [13], in that a type II B turn with Gly312 in the i + 1 and Ala313 in the i + 2 position would also be expected to be a competent thrombin-like proteolytic substrate. Alternatively, the type VI turn could be maintained in the P313A variant, as recently observed for a carbonic anhydrase II variant [36]. We suggest that this shift is essential for V, loop cleavage by thrombin, factor Xa, or related proteases.…”
Section: Discussionsupporting
confidence: 71%
“…Presumably, the total dimerization interface area is large enough to tolerate the single amino acid changes, and the cis-peptide bond configuration in P89A was retained. This retention is not completely unexpected and has been observed in several other cases (30,31). To verify SR␤-specific homodimerization, we performed the gel-filtration assay with SR␤ from three additional organisms: Drosophila melanogaster, Caenorhabditis elegans, and Homo sapiens.…”
Section: Sr␤ Homodimerization In Vitrosupporting
confidence: 59%
“…Sci. USA 94 (1997)demonstrated unequivocally by the solution of its crystal structure (47), which showed that the cis peptide bond is retained in the mutant. During the folding of these proteins, it is likely that the local formation of ''native-like'' structure in the vicinity of the cis peptide bond provides stabilizing interactions (such as hydrogen bonds, metal ligand binding, etc.)…”
Section: Resultsmentioning
confidence: 99%